Studi Bioekologi Kerang Simping (Amusium pleuronectes) di Perairan Semarang dan Kendal - Nursalim, Haviz Rachman; Suprijanto, Jusup; Widowati, Ita (977-2407769)
Asian Moon Scallop (Amusium pleuronectes) is one of scallop species which catch as the secondary crops of the fishing activity. This condition need to understand his biological background, such as the relationship between length and weight, growth, condition index and gonad index. The research purpose is to identify the relationship between length and weight, growth, condition index and gonad index of the Asian Moon Scallop, collected from the Semarang and Kendal Waters. This research was carried out from June to July, 2011 in the Semarang and Kendal waters. Three times collections was done during the research period. A total of 594 individuals of Asian Moon Scallop were collected, which determined there shell length, height, thickness and the total weight. Measurement and observation processes were held in Biology Laboratory, Faculty of Fishery and Marine Diponegoro University, Semarang. The descriptive-explorative methods was used as the research method. While the purposive sampling was applied as the data collection method, and determined the research site. The Asian Moon Scallop growth was determined using the nisbi mothod. The relationship between length and weight, condition index and gonad index were also determined. The b constanta show the value of 3.070, 2.853 and 2.862, which show that the length and weight relationship of Asian Moon Scallop is isometric and alometric negative. The Asian Moon Scallop growth with nisbi method show an equation of 1 cm for the shell length, 0.5 cm for the height, 0.2 sm for the thickness and 5 gr for the total weight of shells. The condition index value of Asian Moon Scallop (A. pleuronectes) is approximately for about 36.01 % - 61.44 %, while the gonad index value is about 8.31 % - 12.09 %.